Predictors and Program Outcomes of Empowering Practices of FFA Chapter Advisors - Kimberly S. Anderson; Lorilee R. Sandmann (Adult Education Research Conference, 2009)
Adults managing youth organizations strive to build partnerships with students in which the shared leadership process results in a sense of empowerment. This research investigates the predictors and programs outcomes of empowering practices used by FFA chapter advisors. Findings provide implications for preservice and continuing education.